Sigma versus Pi

Algebra Level 4

A = n = 0 1000 exp ( ( 1000 n ) ) B = exp ( 3 n = 0 333 ( 999 3 n ) ) A = \prod_{n = 0}^{1000}{\exp \left({\dbinom{1000}{n}} \right)} \ \quad \quad B = \ \exp{\left( 3 \sum^{333}_{n=0}\dbinom{999}{3n} \right) }

Which of the above is larger?

A < B A < B A = B A = B A > B A > B

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Apr 16, 2017

A = n = 0 1000 exp ( 1000 n ) = exp n = 0 1000 ( 1000 n ) = exp ( 2 1000 ) B = exp ( 3 n = 0 333 ( 999 3 n ) ) = exp ( 2 999 2 ) See note. \begin{aligned} A & = \prod_{n=0}^{1000} \exp \dbinom {1000}n = \exp \sum_{n=0}^{1000} \binom{1000}n = \exp \left(2^{1000}\right) \\ B & = \exp \left( 3 \sum_{n=0}^{333} \binom {999}{3n} \right) = \exp \left(2^{999}-2 \right) & \small \color{#3D99F6} \text{See note.} \end{aligned}

Therefore, A > B \boxed{A>B}


Note:

( 1 + 1 ) 3 n = 1 + ( 3 n 1 ) + ( 3 n 2 ) + ( 3 n 3 ) + + ( 3 n 3 n ) ( 1 + ω ) 3 n = 1 + ( 3 n 1 ) ω + ( 3 n 2 ) ω 2 + ( 3 n 3 ) + + ( 3 n 3 n ) ω is the third root of unity. ( 1 + ω 2 ) 3 n = 1 + ( 3 n 1 ) ω 2 + ( 3 n 2 ) ω + ( 3 n 3 ) + + ( 3 n 3 n ) Note that 1 + ω + ω 2 = 0 2 3 n + ( 1 + ω ) 3 n + ( 1 + ω 2 ) 3 n = 3 + 3 ( 3 n 3 ) + 3 ( 3 n 6 ) + 3 ( 3 n 9 ) + + 3 ( 3 n 3 n ) 2 3 n + ( ω 2 ) 3 n + ( ω ) 3 n = 3 k = 0 3 n ( 3 n 3 k ) 3 k = 0 3 n ( 3 n 3 k ) = 2 3 n 2 \small \begin{aligned} (1+1)^{3n} & = 1 + \binom {3n}1 + \binom {3n}2 + \binom {3n}3 + \cdots + \binom {3n}{3n} \\ (1+\omega)^{3n} & = 1 + \binom {3n}1 \omega + \binom {3n}2 \omega^2 + \binom {3n}3 + \cdots + \binom {3n}{3n} & \color{#3D99F6} \omega \text{ is the third root of unity.} \\ (1+\omega^2)^{3n} & = 1 + \binom {3n}1 \omega^2 + \binom {3n}2 \omega + \binom {3n}3 + \cdots + \binom {3n}{3n} & \color{#3D99F6} \text{Note that }1+\omega + \omega^2 = 0 \\ 2^{3n} + (1+\omega)^{3n} + (1+\omega^2)^{3n} & = 3 + 3 \binom {3n}3 + 3 \binom {3n}6 + 3\binom {3n}9 + \cdots + 3\binom {3n}{3n} \\ 2^{3n} + (-\omega^2)^{3n} + (-\omega)^{3n} & = 3 \sum_{k=0}^{3n} \binom {3n}{3k} \\ \implies 3 \sum_{k=0}^{3n} \binom {3n}{3k} & = 2^{3n} - 2 \end{aligned}

Nice solution! Thanks!

Steven Jim - 4 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...